Deciphering the Structure and Function of Nuclear Pores Using Single-Molecule Fluorescence Approaches. Issue 10 (22nd May 2016) - Musser, Siegfried M.; Grünwald, David
Abstract: Due to its central role in macromolecular trafficking and nucleocytoplasmic information transfer, the nuclear pore complex (NPC) has been studied in great detail using a wide spectrum of methods. Consequently, many aspects of its architecture, general function, and role in the life cycle of a cell are well understood. Over the last decade, fluorescence microscopy methods have enabled the real-time visualization of single molecules interacting with and transiting through the NPC, allowing novel questions to be examined with nanometer precision. While initial single-molecule studies focused primarily on import pathways using permeabilized cells, it has recently proven feasible to investigate the export of mRNAs in living cells. Single-molecule assays can address questions that are difficult or impossible to answer by other means, yet the complexity of nucleocytoplasmic transport requires that interpretation be based on a firm genetic, biochemical, and structural foundation. Moreover, conceptually simple single-molecule experiments remain technically challenging, particularly with regard to signal intensity, signal-to-noise ratio, and the analysis of noise, stochasticity, and precision. We discuss nuclear transport issues recently addressed by single-molecule microscopy, evaluate the limits of existing assays and data, and identify open questions for future studies. We expect that single-molecule fluorescence approaches will continue to be applied to outstanding nucleocytoplasmic transport questions, and that the approaches developed for NPC studies are extendable to additional complex systems and pathways within cells. Graphical abstract: Highlights: Nuclear pores mediate macromolecular exchange between the nucleus and cytoplasm. A network of intrinsically disordered polypeptides forms the permeability barrier. Single-molecule fluorescence approaches have enabled biophysical characterization. Transport complex assembly and disassembly occur in vestibules at the pore exits. Future single-molecule studies are needed to resolve numerous outstanding problems.